Study of Coronary Arteries’ Atherosclerosis in Autopsies Conducted at BPS GMC (W), Khanpur Kalan, Sonipat (Indian Internet Journal of Forensic Medicine and Toxicology, 2023)
Background: Atherosclerosis is a leading cause of vascular disease worldwide. Its major clinical manifestations include ischemic heart disease, ischemic stroke, and peripheral arterial disease. In view of the above-mentioned disease load, this study was carried out at tertiary care hospital in north India (Haryana region) from year 2021 to 2022. A total of 80 cases were included in this study which was brought for postmortem examination. Material and Methods: In the present study, 80 patients were studied who came for postmortem at tertiary care hospital in north India from year 2021 to 2022. In these 80 cases, along with gross examination of hearts, 240 main coronary arteries, that is, left coronary artery (LCA), left anterior descending artery (LAD) and right coronary artery (RCA), were studied both grossly and microscopically, using conventional staining methods and light microscopy. Grading of coronary arteries’ atherosclerosis was given according to the Modified American Heart Association Classification. Result: Among 80 postmortem cases, 63cases were males and 17 were females. Peak occurrence of Coronary arteries’ atherosclerosis was noted in the age groups of 30–39 and 40–49 years as the number of study cases were most in these age groups. Number of coronaries involved and severity of lesions increased with increasing age. Percentage of lesions in males was significantly more as compared with females. LAD and LCA involvement was almost similar but more than RCA.
Keywords: Atherosclerosis; MAHA; Coronary arteries; lifestyle; LAD; RCA; LCA